Neutron interferometric measurement and calculations of a phase shift induced by Laue transmission. Issue 5 (21st July 2015) - Potocar, T.; Zawisky, M.; Lemmel, H.; Springer, J.; Suda, M.
<x xml:space="preserve">Abstract</x> This study investigates the phase shift induced by Laue transmission in a perfect Si crystal blade in unprecedented detail. This `Laue phase' was measured at two wavelengths in the vicinity of the Bragg condition within a neutron interferometer. In particular, the sensitivity of the Laue phase to the alignment of the monochromator and interferometer (rocking angle) and beam divergence has been verified. However, the influence of fundamental quantities, such as the neutron–electron scattering length, on the Laue phase is rather small. The fascinating steep phase slope of 5.5° [(220) Bragg peak] and 11.5° [(440) Bragg peak] per 0.001 arcsec deviation from the Bragg angle has been achieved. The results are analysed using an upgraded simulation tool.